Model Konseling Eklektik dalam Pendidikan Perspektif Al-Qur`an - Darwis Hude; Ahmad Husnul Hakim; Dedi Kusmayadi (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
The conclusion of this research is that eclectic counseling in Al-Qur'an perspective education is a counseling model that integrates directive and non-directive counseling based on Qur'anic reasoning which provides guidance or teaching regarding life guidelines for a person to be able to live his life properly and correctly. and able to overcome all the problems of life they face. The interesting thing found in this study is a new counseling approach called Qur’an eclectic counseling (Qur’an eclectic counseling), which is a counseling approach model that integrates the stages of counseling listening, observing, understanding, and providing solutions with counseling techniques. resilience, contemplation, and dialogue selectively and practically.